Microencapsulation of Lime Peel Essential Oils (Citrus aurantifolia) with Complex Coacervation Methods using Gelatin/Sodium Alginate Coating - Sandra Puspita; Diana Rakhmawaty Eddy; Tatang Wahyudi; Euis Julaeha (Syarif Hidayatullah State Islamic University, 2020)
Lime (Citrus aurantifolia) peel essential oils are complex metabolites mainly used as natural preservatives. The principal constituents include d-limonene, β-pinene, and terpineol. Moreover, essential oils (EOs) are potentially known volatile and unstable compounds, hence, they require proper packaging techniques, e.g., microencapsulation. The purpose of this study is to evaluate the binary methods of lime peel essential oils microencapsulation using complex coacervation. This involves the application of gelatin and sodium alginate coatings under two specific conditions, termed core/coating ratio 1:1.2, with modified stirring and core/coating ratio 1:2.0, with stirring speed of 600 rpm, respectively. The results showed the EOs preparation generated 0.70% yield characterized by good quality, fresh aroma, and pale-yellow coloration. Also, microcapsules delivered 37.06% yield, 39.18% oil content, 31.53% encapsulation efficiency (EE), and less smooth-edged SEM surface under condition I. Meanwhile, condition II demonstrated 51.46% yield, 58.66% oil content, 92.04% encapsulation efficiency (EE), and flat-curved, SEM surface. Furthermore, it was carefully observed condition II produced more superior microcapsules